2021
DOI: 10.1002/agt2.93
|View full text |Cite
|
Sign up to set email alerts
|

Rational design for thermochromic luminescence in amorphous polystyrene films with bis‐o‐carborane‐substituted enhanced conjugated molecule having aggregation‐induced luminochromism

Abstract: We designed the triad molecule, bis-o-carborane-substituted bis(thienylethynyl) benzene, as a filler for realizing thermochromic luminescent behaviors based on conventional polymer films, such as polystyrene. From the optical measurements, it was found that the triad can show solid-state emission and dual-luminescent properties with variable intensity ratios depending on media. From the mechanistic studies including the experiments with the methyl-substituted model compound, it was revealed that dual emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…30 Moreover, by introducing bis-o-carborane substituents, highly sensitive luminochromic behaviors were observed. 31,32 The bis-o-carboranesubstituted pyrene triad showed clear luminochromic behaviors just by touching the crystalline powder. 32 Because of steric hindrances of o-carboranes, defect sites in crystalline packing could be readily induced by weak stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…30 Moreover, by introducing bis-o-carborane substituents, highly sensitive luminochromic behaviors were observed. 31,32 The bis-o-carboranesubstituted pyrene triad showed clear luminochromic behaviors just by touching the crystalline powder. 32 Because of steric hindrances of o-carboranes, defect sites in crystalline packing could be readily induced by weak stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…[20] More recently, we reported thermochromic luminescent behaviors of bis(thienylethynyl)benzene-based o-carborane in amorphous polystyrene films. [21] By the aggregation formation of o-carborane species in polymer matrices, luminescent chromic behaviors originating from the enhancement of ICT emission were observed. Although the changes in intensity ratio were slight, clear luminescent chromic behaviors can be exhibited owing to dual-luminescent nature.…”
Section: Introductionmentioning
confidence: 99%
“…Our group also reported that the triaryl‐substituted o ‐carborane derivative can show white‐light emission in the specific aggregation state [20] . More recently, we reported thermochromic luminescent behaviors of bis(thienylethynyl)benzene‐based o ‐carborane in amorphous polystyrene films [21] . By the aggregation formation of o ‐carborane species in polymer matrices, luminescent chromic behaviors originating from the enhancement of ICT emission were observed.…”
Section: Introductionmentioning
confidence: 64%
“…[20] More recently, we reported thermochromic luminescent behaviors of bis(thienylethynyl)benzene-based o-carborane in amorphous polystyrene films. [21] By the aggregation formation of o-carborane species in polymer matrices, luminescent chromic behaviors originating from the enhancement of ICT emission were observed. Although the changes in intensity ratio were slight, clear luminescent chromic behaviors can be exhibited owing to the dual-luminescent nature.…”
Section: Introductionmentioning
confidence: 99%